THE IMPLEMENTATION OF REVITALIZATION POLICY IN VOCATIONAL HIGHER EDUCATION PROGRAM/IMPLEMENTASI KEBIJAKAN REVITALISASI PENDIDIKAN TINGGI VOKASI PROGRAM DIPLOMA III - Rani Intan (Jurnal Pengabdian Vokasi, 2022)
Revitalization of Vocational Higher Education aims to create higher education graduates who have the competence, qualifications, and skills that link and match with the needs of the industrial world and the world of work/business (DUDI). The purpose of the study was to analyze the efforts to optimize the management of study programs through the revitalization of vocational education with the object of research being the Diploma III Administrative Management, Mechanical Engineering, Civil Engineering and Computer Engineering at the Islamic University "45" Bekasi. The research uses a qualitative approach with interviews, observation and document studies. The findings obtained from this study are that several elements dan criterias  in the implementation of revitalization programs have not been fulfilled that impact on; the quality and learning methods that do not support the skills of students and graduates in adapt to the world of business and industry, curriculum and learning outcomes that do not link and match with the needs of the business world and industry, practicum facilities that have not been maximized in supporting the learning process, partnership programs that have not been fully implemented, and most of the graduates are not directly absorbed in the world of work. For this reason, the study program needs to optimize management by implementing the Vocational Higher Education Revitalization Framework that has been set by the Ministry of Higher Education, Directorate General of Vocational Studies, associations of vocational universities and DUDI.